Cross-country determinants of life satisfaction: Exploring different determinants across groups in society - Christian Bjørnskov; Axel Dreher; Justina A. V. Fischer (ETH Zurich, KOF Swiss Economic Institute, 2006)
This paper explores a wide range of cross-country determinants of life satisfaction exploiting a database of 90,000 observations in 70 countries. We distinguish four groups of aggregate variables as potential determinants of satisfaction: political, economic, institutional, and human development and culture. We use ordered probit to investigate the importance of these variables on individual life satisfaction and test the robustness of our results with Extreme Bounds Analysis. The results show that only a small number of factors, such as openness, business climate, postcommunism, the number of chambers in parliament, Christian majority, and infant mortality robustly influence life satisfaction across countries while the importance of many variables suggested in the previous literature is not confirmed. This remains largely true when the analysis splits national populations according to gender, income and political orientation also.
Keywords: I31; H10; H40; 330; Life Satisfaction; Happiness; Institutions; Extreme Bounds Analysis; Sozialer Status; Schätzung; Zufriedenheit